They Knew: The US Federal Government$1 (Bs Fifty-Year Role in Causing the Climate Crisiss - Speth, James Gustave (Cambridge, Massachusetts : The MIT Press, 2021)
"In 2015, a group of 21 young people came together to sue the federal government for violating their constitutional rights by promoting the climate catastrophe that has already begun to deprive them of life, liberty and property without due process of law. The path breaking litigation, Juliana v United States, has had more success in the courts than many expected, but the federal government has repeatedly delayed the case from getting to trial. The case is now pending before the Ninth Circuit Court of Appeals. Whatever its judicial outcome, the litigation has received a great deal of media attention and public acclaim. Youth activists now central to climate advocacy say that they were influenced by this early example of young people stepping up. Our Children's Trust (OCT), the group that has brought the children's climate lawsuit, has now authorized the author, Gus Speth, to proceed with publication of an updated, 2020 version of the Expert Report he prepared for the litigation in 2018. The original Speth report was prepared in his capacity as an expert in the subject. In the view of many who have seen it, the report is the most compelling indictment of federal climate action and inaction yet written"
Keywords: Environmental policy -- History -- 20th century -- 21st century -- United States; Climatic changes -- History -- 20th century -- 21st century -- United States